2004
DOI: 10.1002/per.513
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of self‐regulation and the Big Five

Abstract: The authors examined relations between self-regulatory properties of personality (egocontrol and ego-resilience) and the Big Five. Ego-control and ego-resilience were independent predictors of each Big Five dimension. Additionally, cluster analysis suggested four replicable 'types'. Participants in the first (largest) cluster reported the highest levels of resilience and moderately low levels of control. The second cluster reported aboveaverage resilience and high control. The third cluster reported below-aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 56 publications
3
84
0
Order By: Relevance
“…self-reinforcement: see e.g. Gramzow et al, 2004;O'Connor, 2002). While these findings lend indirect support for the notion that Type B individuals often report feeling healthier than their Type A counterparts (e.g.…”
Section: Notesmentioning
confidence: 80%
“…self-reinforcement: see e.g. Gramzow et al, 2004;O'Connor, 2002). While these findings lend indirect support for the notion that Type B individuals often report feeling healthier than their Type A counterparts (e.g.…”
Section: Notesmentioning
confidence: 80%
“…John (1990) suggested that the Block and Block traits of ego-resilience and ego-control were more abstract than the Big Five. Gramzow et al (2004) found that ego-control and ego-resilience were independent predictors of the Big Five. Of course, three factor models have also been suggested at a super-ordinate level (e.g., Eysenck 1981; Rothbart and Bates 1998; Watson et al 1994).…”
Section: Discussionmentioning
confidence: 94%
“…Consistently, overcontrol and undercontrol profiles are conceptualized as corresponding to two opposing poles on the ego‐control dimension. Despite inconsistencies in previous studies, researchers largely agree that undercontrol groups are represented by high scores in Extraversion and Openness, while overcontrol groups tend to score low on these traits (Robins et al, ; Ekehammar & Akrami, ; Gramzow et al, ). This pattern is replicated in the current analyses, with an additional distinction between profiles regarding the trait Honesty/humility (reflecting tendencies towards restraint/inhibition), which presents as high in overcontrollers and low in undercontrollers.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, the most well-replicated finding among researchers using the person-centred approach is the production of three personality profiles (Caspi, 1998;Asendorpf et al, 2001). However, it has been argued that this threeprofile model overlooks key distinctions between personality types, and that a four-profile model provides a better foundation for a more substantive theoretical interpretation of the structures (Gramzow, Sedikides, & Panter, 2004).…”
mentioning
confidence: 99%